2012
DOI: 10.1016/j.taap.2012.08.031
|View full text |Cite
|
Sign up to set email alerts
|

PON1 status does not influence cholinesterase activity in Egyptian agricultural workers exposed to chlorpyrifos

Abstract: Animal studies have shown that paraoxonase 1 (PON1) genotype can influence susceptibility to the organophosphorus pesticide chlorpyrifos (CPF). However, Monte Carlo analysis suggests that PON1 genotype may not affect CPF-related toxicity at low exposure conditions in humans. The current study sought to determine the influence of PON1 genotype on the activity of blood cholinesterase as well as the effect of CPF exposure on serum PON1 in workers occupationally exposed to CPF. Saliva, blood and urine were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 47 publications
(72 reference statements)
3
9
0
Order By: Relevance
“…However, there was no significant contribution of other predictors considered in this study to enzyme activity. Although ChE activity is a important parameter to reflect OP exposure, there was no significant contribution of ChE activity to PON1 activities, which is in line with the results from Ellison et al 40 So far there are some investigations of the association between PON1 polymorphisms and risk of diseases (such as coronary heart disease, diabetes mellitus and cerebral infarction) in the Chinese population, [41][42][43] but there is little information on PON1 activity and the association between PON1 status and sensitivity to OP toxicity in the Chinese population who are occupationally exposed to pesticides. Our current investigation might be the first study to show an association between PON1 polymorphisms and susceptibility to OP toxicity in China.…”
Section: Discussionsupporting
confidence: 90%
“…However, there was no significant contribution of other predictors considered in this study to enzyme activity. Although ChE activity is a important parameter to reflect OP exposure, there was no significant contribution of ChE activity to PON1 activities, which is in line with the results from Ellison et al 40 So far there are some investigations of the association between PON1 polymorphisms and risk of diseases (such as coronary heart disease, diabetes mellitus and cerebral infarction) in the Chinese population, [41][42][43] but there is little information on PON1 activity and the association between PON1 status and sensitivity to OP toxicity in the Chinese population who are occupationally exposed to pesticides. Our current investigation might be the first study to show an association between PON1 polymorphisms and susceptibility to OP toxicity in China.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, in the case of a single applicator and non-applicator, there's an 86.6 % (95 % CI: 75.0–98.3 %) chance the applicator would have a higher TCPy concentration. Figure 1 shows that the average TCPy levels for adolescent applicators and non-applicators in the current study are similar to those found for adult pesticide applicators and non-applicators from the same region in August 2009 (adult data from, Ellison et al 2012). The Egyptian applicators and non-applicators had much higher urinary TCPy levels than the geometric mean for adolescents (12–19 years) reported in National Health and Nutrition Examination Survey (Centers for Disease Control and Prevention 2009).…”
Section: Resultssupporting
confidence: 73%
“…Additional research in this adolescent population provides further evidence of environmental exposure; an increase in TCPy levels, above baseline, was found in both applicator and non-applicator groups during the application season, with a significantly greater increase in the applicator population (Crane et al 2013). Although elevated levels were found in the adolescent applicators compared to the non-applicators, they are similar to the levels reported in adult pesticide workers in Egypt in August 2009 (Ellison et al 2012), but are markedly less than observed in adult applicators in 2008 (Farahat et al 2011). The variability in occupational exposures observed in adult applicators in part reflects the year-to-year variation in the use of pesticides on cotton fields.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations